Pandangan Islamic Economic Ethics Terhadap Dimensi Individualisme Dalam Ekonomi Kapitalis - Setiawan Bin Lahuri; Lamya Nurul Fadhilah; Imam Kamaluddin (el-Jizya: Jurnal Ekonomi Islam, 2022)
Monopolies and stockpiling in business are clear evidence of human greed stemming from capitalist individualism. Despite the bad impact, the majority of people will prefer and support individual freedom without being limited by regulations. Thus, amid intense competition in the capitalist economy, Islamic ethics is present in the business environment to provide guidance and offer approaches that are in line with the ethical values ​​adopted by society. This study aims to find out: 1) the similarities and differences between individualism in capitalism and Islam, 2) the moral views of Islamic economics on capitalist individualism. The research method uses descriptive qualitative and the main variables in this study are capitalist individualism and Islamic economic ethics. Based on the results of the research analysis shows that: 1) Mostly, the dimensions of individualism in capitalism and Islam are different. 2) The biggest difference lies in the orientation, where the capitalist is oriented to the quantity of material (materialistic) and rationality, while Islam is oriented to the balance of the world and the hereafter. 3) Islam is very synonymous with ethics or morals that are oriented to the Qur'an and Hadith, while capitalists adhere to the principles of self-interest and rationality. 4) While the similarities between the two lie in the recognition of individual ownership and enthusiasm in working or doing business.